Manajemen Hubungan Masyarakat (Humas) dalam Meningkatkan Minat Masyarakat di Pondok Pesantren Mamba'us Sholihin Suci Manyar Gresik - Zunaida, Laily; Aulia, Maulidiah Amirul (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2023)
Connection Public is communication two direction Among organization with public in a manner lead come back in framework support function and purpose management with increase coaching cooperation and fulfillment interest together . So activity connection society inside _ a organization is the activities in it aim for absorb perceived problem _ by Public and convey to staff or leader cottage boarding school as well as activity communicate all lodge programs boarding school to society . By because that cottage boarding school no can life without exists work same with society . Cottage boarding school no only need Public in Thing absorption graduate of course , more from that cottage boarding school also need Public for entrust his sons and daughters enter go to school lodged boarding school, and also environment cottage surrounded boarding school by Public local . Look so importance role Public for cottage boarding school , then party cottage boarding school must capable manage connection with Public with ok . Connection cooperation this need a management . Management is a typical process , consisting from activity planning , organizing , actuating , and supervision, that conducted for determine as well as reach goals or goals that have been set . As for the research focus in study this , ie How Management PR in Increase Interest Public and How Interest Public after there is Management PR as well as What Just Factor inhibitor and Supporters in Management Public Relations at Pondok Boarding school Mamba'us Sholihin Holy Manyar Gresik. Purpose study among others for describe and know management public relations as well as factor supporters and block in the hut boarding school Mamba'us Sholihin Holy Manyar Gresik. Study and approach in study this is study qualitative research qualitative is characteristic research _ descriptive . Results obtained _ is Management PR as well as activities public relations in increase interest the community at the boarding school Mamba'us Sholihin Holy Manyar Gresik is running with good interest